Radiation-Induced Brachial Plexopathy in Breast Cancer and the Role of Surgical Treatment - Kıbıcı, Kenan; Erok, Berrin; Atca, Ali Önder (Indian Journal of Neurosurgery, 2020)
Objective We aimed to evaluate improvement in the pain, motor, and sensory functions after neurosurgical intervention, by objective methods in patients with radiation-induced brachial plexopathy (RIBP), as a complication of radiotherapy (RT).Materials and Methods In our study, 11 patients, who experienced grade 3 or 4 brachial plexopathy according to the LENT-SOMA (late effects of normal tissue—subjective, objective, management, analytic) side-effect index, as a complication of RT which was performed after being operated for breast cancer, were included. In the postoperative period pain, sensation, and motor function loss were followed.Results There was apparent regression in the pain. The mean visual analogue scale (VAS) value decreased to 4 from the preoperative VAS value of 9.4. However, no significant improvement was observed in either sensory and motor functions.Conclusion RIBP is a progressive disease in breast cancer patients after radiotherapy. Evaluation of the results of applied surgical treatments and changes in the results with time is important to direct the treatment. Neurolysis should only be considered when other treatment methods fail and should be considered as an irreversible and potentially permanent procedure.
Keywords: radiation-induced brachial plexopathy; neurolysis; radiotherapy; breast cancer